The graph should look the the one I attached to this answer
Answer:
-50
Step-by-step explanation:
-32 + ( -18 )
= - 32 - 18
= -50
Hope this helps!
(-2+8i)x(3-10i)
-2 x 3 - 2 x (-10i) +8i x 3- 8i x 10i
-6+20i+24i - 80i ^2
-6+20i+24i - 80 x (-1)
-6+20i+24i + 80
Answer: 74+44i
Answer:
see explanation
Step-by-step explanation:
If A +B = 45° then tan(A+B) = tan45° = 1
Expanding (1 + tanA)(1 + tanB)
= 1 + tanA + tanB + tanAtanB → (1)
Using the Addition formula for tan(A + B)
tan(A+B) = = 1 ← from above
Hence
tanA + tanB = 1 - tanAtanB ( add tanAtanB to both sides )
tanA + tanB + tanAtanB = 1 ( add 1 to both sides )
1 + tanA + tanB + tanAtanB = 2
Then from (1)
(1 + tanA)(1 + tanB) = 2 ⇒ proven
Answer:
The graph of f(x) = x² was transformed to create the graph of g(x) = f(x) + 1.5. Which statement about the graphs is true?
The vertex of the graph of g is 1.5 units to the left of
the vertex of the graph of f.
B
The y-intercept of the graph of g is 1.5 units above the
y-intercept of the graph of f.
The graph of g is a reflection of the graph of f across
the y-axis.
The graph of g is a reflection of the graph of f across
the x-axis.
Step-by-step explanation: